THE USE OF METHANOLIC EXTRACT OF BOSWELLIA SERRATA IN COMBINATION WITH DEXTRIN AND GLYCERIN FOR TREATMENT OF EXPERIMENTALLY INDUCED THERMAL INJURIES IN RABBITS (Iraqi Journal of Medical Sciences, 2017)
Background: Thermal injuries and burns are considered as the major health care problem worldwide. Burns in general are life-threatening condition with high morbidity and mortality. Wound infection and delayed wound healing are the main essential problems in burned patients and represent the major goals for new therapeutic strategies. Frankincense, the gum resin of the Boswellia serrata tree have traditionally been used in folk medicine for centuries to manage different chronic inflammatory diseases, the anti-inflammatory potential of lipophilic Boswellia serrata extracts were confirmed by experimental data from animal models and clinical studies on humans. Objective: Comparing the wound healing effect of methanol extract of Boswellia serrata-dextrin-glycerin combination to that of silver sulfadiazine.Methods: The dried powder of the oleo gum resin was extracted by cold method (maceration) using methanol and then the dried extract was mixed with dextrin and glycerin (30 gm, 40 ml, 60 gm) respectively. Thirty-two domestic male rabbits were divided into four groups, eight animals for each group, the groups were; intact healthy (H), burned without treatment (Gr1), burned and treated with silver sulfadiazine (Gr2) and burned and treated with the methanolic extract of Boswellia serrata–dextrin-glycerin combination (Gr3). Thermal injury was induced in all groups (except the intact healthy group) and treated topically on burned area once daily for 28 days. Tissue levels of vascular endothelial cell growth factor (VEGF) and tumor necrosis factor alpha (TNF-?) were assessed in addition to skin histological examination at the end of the study (day 29). Results: Histopathological evaluation showed enhanced inflammatory response, granulation tissue formation, and collagen deposition due to the appropriate regulation of TNF-? and VEGF.Conclusion: Topical use of the methanolic extract of Boswellia serrata-dextrin-glycerin combination significantly enhanced wound healing activities.Keywords: Boswellia serrata, VEGF, TNF, thermal injury DOI: 10.22578/IJMS.14.3.13
Keywords: Boswellia serrata; VEGF; TNF; thermal injury